Multi-Output Productivity Change for Korean Agriculture: Non-Frontier Primal Measure with Farm-Level Panel Data - 강혜정 (한국농촌경제연구원, 2007)
This paper analyzes the productivity growth in Korean agriculture with data on multiple crops over the five years from 1998 to 2002. Measurements are obtained from the estimation of a non-frontier multi-output production function. Multi-output production technology is characterized with a transformation function. For empirical analysis, this study employs the generalized linear transformation function, which extends a linear functional form by allowing a full set of interactions among arguments in the function. The results find that technological change has led a significant productivity change. Larger farms experience the highest rate of productivity growth by the greatest rate of scale effect. More human capital also leads higher productivity growth rates.
Keywords: multi-output production technology; productivity change; transformation function; panel data; multi-output production technology; productivity change; transformation function; panel data